Vascular stents: The most important types and characteristics - Drakul Dragana; Matić Predrag; Drobac Milica; Kostić Nađa; Vemić Ana; Vasiljević Dragana; Malenović Anđelija (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Vascular stents are general medical devices of class III or IIb, which are placed along the walls of the constricted coronary and peripheral blood vessels thus keeping them viable. According to the mechanism of expansion, stents may be balloon-expandable or self-expanding. Depending on the geometry they can be classified into: coil stents, open-cell modular stents and multi-cell closed cell stents. The most important characteristic of vascular stents is their flexibility, but a number of additional requirements must also be met: high radial strength, low elastic deformation, small diameter, the possibility of monitoring through the bloodstream, minimum subsequent shortening, minimum elastic longitudinal deformation, and the optimal retention at target site. Materials for production of stents must be biologically inert, visible by radiological techniques, biocompatible, corrosion-resistant and resistant to stress due to blood flow. The most significant adverse event after stent implantation is the occurrence of restenosis, which is most efficiently overcome by the application of drug releasing stents. These stents are composed of three parts: stent platform, drug carrier and a drug that inhibits neointimal hyperplasia - paclitaxel and limuses (sirolimus, everolimus, zotarolimus, tacrolimus, pimecrolimus, etc.). In recent years, stents with surfaces coated with substances that accelerate endothelialisation and thus reduce thrombosis have been developed. The latest approach is represented by a stent with the lumen coated with CD34 antibody, and the outer side coated with sirolimus. By using these devices a double effect is achieved: acceleration of endothelialisation and inhibition of neointimal hyperplasia.